Estimation of probabilities for ordered sets and application to calibration of rating models - Gustavo F. Serenelli; Emiliano Delfau (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
The goal of this document is to present a methodology for estimating probabilities for ordered sets. This may have several practical applications such as calibration of Rating Models, estimation of Mortality Tables or measurement of side effects related to different doze sizes. In order to do this, an Objective / Non Informative Bayesian approach is applied, through which, using a multidimensional Jeffreys prior, a posterior distribution may be inferred for each of the probabilities being estimated.
Keywords: 330; Bayesian estimation; probability estimation; uninformative prior; rating calibration; low default; ordered sets; jeffreys prior